2011
DOI: 10.1111/j.1525-1470.2011.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Meningothelial Hamartoma of the Scalp in a 9‐Year‐Old Child

Abstract: Meningothelial hamartomas represent a collection of meningothelial elements in an ectopic location. Lesions are histologically characterized as a proliferation of connective tissue elements and small- and medium-sized vessels admixed with meningothelial elements. Lesions are most often located on the scalp, present at birth, and do not extend past the subcutis. We discuss the case of a 9-year-old African American girl presenting with one such lesion on the parietal aspect of the scalp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…It generally presents at birth or in early childhood, with no clear sex or race predilection. To our knowledge, 18 cases have been reported in the international literature . The origin of this hamartoma has yet to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It generally presents at birth or in early childhood, with no clear sex or race predilection. To our knowledge, 18 cases have been reported in the international literature . The origin of this hamartoma has yet to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…It might arise from ectopic arachnoid cells displaced during embryogenesis. Alternatively, it could result from a cellular abortive migration from the neural crest or from an extrusion through a pathologic extracranial connection . The clinical behavior is benign and surgical excision is curative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other terms, such as rudimentary meningocele and primary cutaneous meningioma , have also been used in the literature to describe these lesions. A recent review of 16 cases by Curran‐Melendez et al revealed that meningothelial hamartomas arise primarily on the posterior scalp, although lesions on the forehead have been reported. Most lesions are found in young children, with a few reports in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue masses of the scalp are commonly encountered in clinical practice. Among these, lipoma is the most common benign tumor; only 13% of them are seen in the head and neck [1]. Nevertheless, the incidence of lipoma on the scalp comprises 30%, followed by that of trichilemmal cysts [2].…”
Section: Introductionmentioning
confidence: 99%